Amputations and socioeconomic position among persons with diabetes mellitus, a population-based register study. Issue 4 (8th April 2013) - Venermo, Maarit; Manderbacka, Kristiina; Ikonen, Tuija; Keskimäki, Ilmo; Winell, Klas; Sund, Reijo
Abstract : Objective: Low socioeconomic position is a known health risk. Our study aims to evaluate the association between socioeconomic position (SEP) and lower limb amputations among persons with diabetes mellitus. Design: Population-based register study. Setting: Finland, nationwide individual-level data. Participants: All persons in Finland with any record of diabetes in the national health and population registers from 1991 to 2007 (FinDM II database). Methods: Three outcome indicators were measured: the incidence of first major amputation, the ratio of first minor/major amputations and the 2-year survival with preserved leg after the first minor amputation. SEP was measured using income fifths. The data were analysed using Poisson and Cox regression as well as age-standardised ratios. Results: The risk ratio of the first major amputation in the lowest SEP group was 2.16 (95% CI 1.95 to 2.38) times higher than the risk in the highest SEP group (p<0.001). The incidence of first major amputation decreased by more than 50% in all SEP groups from 1993 to 2007, but there was a stronger relative decrease in the highest compared with the lowest SEP group (p=0.0053). Likewise, a clear gradient was detected in the ratio of first minor/major amputations: the higher the SEP group, the higher the ratio. After the first minor amputation, the 2-year and 10-year amputation-free survival rates were 55.8% and 9.3% in the lowest and 78.9% and 32.3% in the highest SEP group, respectively. Conclusions: According to all indicators used, lower SEP was associated with worse outcomes in the population with diabetes. Greater attention should be paid to prevention of diabetes complications, adherence to treatment guidelines and access to the established pathways for early expert assessment when diabetic complications arise, with a special attention to patients from lower SEP groups.